Pore characteristics and fractal characterization variability of typical middle- and high-rank coal reserves: A case study of middle- and high-rank coal samples in western Guizhou - Lou, Yi; Su, Yuliang; Gao, Wei; Wang, Wendong; Xiong, Wei; Chen, Jie; Xia, Peng (Frontiers in Energy Research, 2022)
This article is focused on the study of pore structure characteristics of Songhe and Linhua coal samples based on mercury injection experiment and high-pressure isothermal adsorption experiment. The results show that the pore structure of coal samples in the two mining areas is obviously different under the influence of metamorphic degree. The pores of Songhe mine coal samples, which are characteristic of middle rank coal reserves, are predominantly open cylindrical pores with good connectivity of medium-to-large pores but poor absorption capacity. The tiny and medium pores of Linhua coal samples, which are characteristic of high-level coal reserve, have poor connectivity, dominated by conical pores with mostly closed and semi-closed pores. The pore size distribution of the middle rank coal sample is multi-peaked, with better developed pore sizes, while the pore size distribution of the Linhua coal sample is bi-peaked, with micro and small pores developed. The pore fractal shape of high rank coal reserve is higher than that of middle rank coal reserve, and the complexity of permeable pore space and diffuse pore space of high-order coal reservoir is higher than that of middle-order coal reservoir.